CORPORATE SOCIAL RESPONSIBILITY IN THE COAL-MINING INDUSTRY - T. N. Martynova; L. M. Buldygina; M. S. Ivanov; N. N. Ravochkin (Финансы: теория и практика, 2017)
Article Retracted.Current trends of social and economic development of the country demand from the management and the personnel of the organizations of the fast adaptation and adaptation to the changing conditions. In turn, it demands the weighed personnel policy at the enterprise for the purpose of design of organizational system which would be connected with the solution of the main problems of human resource management at an appropriate level. Long time the economy of our country was planned, that is all enterprises were in state ownership, and their activity was regulated at the level of public administration. For this reason, to each certain head of need wasn’t independent to make strategic administrative decisions. With reorientation of the country to the market relations the situation changed, and in the majority of the enterprises there were private owners.The article demonstrates some aspects of the coal enterprises staff image in the current socio-economic conditions. The problems associated with psychological readiness management personnel for being in corporate social responsibility. The analysis of the specificity of image management of the coal industry is presented.